Space, Culture, and the Youth in Iran - Payvar, Behnoosh. author. aut Link
XXXIX, 190 p.
Keywords: This book analyzes the Artists' House, a cultural center in Tehran, to place Iran's social and cultural transformation in a local-global context. The text addresses the interaction of Iranian youth with technology and mass communications, law, tradition, and contemporary questions concerning body, identity, and lifestyle.